Gestando uma "profissão relativamente nova": a Educação Física na Escola de Aperfeiçoamento (Belo Horizonte, 1927-1945) - Ramona Mendes Fontoura de Morais (2015)
This study focuses on the effects of Physical Education in the development of the teachers of the Training and Development School of Belo Horizonte. The period in time established for this study starts in 1927, the time when the Primary Education Reform was enforced in the State of Minas Gerais, having as one of its aims the establishment of the school. The institution, which went into operation in 1929, was intended for the improvement, from a scientific point of view, of the development and education of primary State School teachers. In 1945, the last group of students graduated from the School, which marks the end of the time period established by this study. Along its 17 years, the Training and Development School boasted the title of escola novidadeira (mould-breaking school), symbolically referring to its renewed education methodology. In the decade of 1920s, the learner-centered and humanistic ideals, known as escolanovismo, are disseminated as the main principles in the development and education of teachers, and this institution, which resulted from this context, appears as the door opened to the realization of the desire to align the development of teachers with the principles proposed for a modern pedagogy. Physical Education, a subject included in the curriculum of this education institution, also finds itself imbued with this ideal. Within this movement, the idea was to make it clear how the Training and Development School cultivated the need to qualify Physical Education teachers. In order to offer a clearer understanding of the teaching methodology used in Physical Education, it was essential to study the actions by Renato Eloy de Andrade and Guiomar Meirelles Becker, teachers of the School and of its Intensive Courses. It was also essential to pay close attention to the different forms of appropriation of the method adopted there, by focusing on the path followed by the schools former student, Diumira Campos de Paiva, and on the data registered by Alzira Farnezzi, a former student of the Intensive Course. The sources investigated were mainly the States official documents. Added to these materials, the thesis on Physical Education in the primary school, presented in the 7th National Conference of Education in 1935, was investigated for this study as well as the Pedagogical Bulletin no.18, the journal A Voz da Escola, the magazine Educando and the book Educação Física Infantil (Physical Education for Children) of the Training and Development School. It was concluded that the discourse that emerged for the subject in the articles written by the teachers, in the materials produced in the intensive courses and in the curriculum of the School, Physical Education was structured to be in line with the New School Principles. Knowledge of childhood, interest in the student as the axis around which the pedagogic work revolves, the teachings of Psychology and Physiology at the basis of the work of the teacher, the games and calisthenics as exercises prescribed for the classes point to the wish for the specialization of the teacher. In conclusion, along with other initiatives at that time, the Training and Development School contributed to the management of Physical Education in Higher Education institutions.